Copper-gallia interaction in Cu-Ga2O3-ZrO2 catalysts for methanol production from carbon oxide(s) hydrogenation - Sanguineti, Pamela Beatriz (2015)
The impact of the interaction between copper and gallia was studied over a selected set of supported(2 wt%) Cu on Ga2O3, ZrO2and Ga2O3–ZrO2catalysts, which were employed in the methanol synthesisfrom CO2and CO mixtures. The higher initial rate of methanol production on the Cu/ZrO2catalyst wasaccompanied by an activity loss of ~35% after 5 h on stream. However, all the gallated catalysts werenotoriously more stable (and selective) than copper on pure zirconia was. Temperature-programmedreduction in H2, X-ray photoelectron spectroscopy and infrared spectroscopy of adsorbed CO resultsproved that temperatures higher than 553 K are needed to completely reduced Cu2+to metallic Cu parti-cles in the gallia-containing catalysts, which was attributed to the formation of a CuGa2O4nanospinel. Theternary Cu–Ga2O3–ZrO2catalysts showed an intermediate behavior, quite dependent on the preparationprotocol, which emphasizes the need for tuning the degree of Cu–oxides interactions. It is suggested thatjust a moderate copper–gallia interaction is beneficial in terms of both activity and selectivity but, also,that a detrimental loss of ‘active’ copper should be avoided.